Electrical charging property of Au nano-particles in a SiON dielectric layer - Lee, Min Seung; Kim, Jae Hoon; Kim, Eun Kyu; Kim, Won Mok (KOREAN PHYSICAL SOC, 2006)
It has been shown that metal nano-particles dispersed in a dielectric layer can be used in nanodevices such as a single electron tunneling transistors and nano-floating gate memories. In this study, we prepared nano-floating gate capacitors by forming Au nano-particles, which were sandwiched between either SiON or SiO2 dielectric layers and we analyzed their electrical characteristics. The SiO2 layers and the Au nano-particles were deposited by RF magnetron sputtering in pure an Ar gas, and SiON layers were deposited in a reactive mode under Ar and N-2 gas mixture. Then, the depositions were carried out at substrate temperature of 300 degrees C and in working pressure of 5 mTorr. The nominal thicknesses of the Au nano-particle were 0.5, 1, and 3 nm and next corresponding average An particle sizes obtained from transmission electron microscopy (TEM) were 3, 4 and 10 nm, respectively.
Keywords: SILICON; MEMORY; OXIDATION; STORAGE; FILMS